PROSPECTIVE SECONDARY METABOLITE OF FAMILI SIMAROUBACEAE - Ari Widiyantoro (Jurnal Penelitian Saintek, 2014)
Simaroubaceae family is a family group of plants that have a primary compound content quasinoids and alkaloids. Family Simaroubaceae spread in tropical regions of Asia, Africa and America. In Asia, family Simaroubaceae widely spread in Southeast Asia, especially Indonesia, Thailand, Vietnam and Malaysia. Some of the families of plants contain secondary metabolites that show promising prospects for use in the fields of health and agriculture that plants are pasak bumi (Eurycoma longifolia Jack), fruit macassar (Brucea javanica L. Merr) and pauh kijang (Irvingia malayana Oliv. Ex. A. Benn). Several compounds were isolated to antiinflamatory test by reduction of inflammation after induced carrageenan, antioxidants test by inhibition of NBT reduction and insecticidal test by antifeedant test on leaf object. The results showed eurycomaside compound from ethyl acetate fraction of the stem bark of Eurycoma longifolia Jack is antiinflammatory by reducing inflammation of 23.56±0.89% after the 10th hour. Dehydrobrusatol compound from ethyl acetate fraction of Brucea javanica L. Merr showed antioxidant activity by inhibition of NBT reduction of 87.65±1.09%. Friedelin compound from the ethyl acetate fraction of the stem bark of Irvingia malayana Oliv ex. A. Benn showed insecticidal activity is antifeedant activity of concentration of 2% with a ratio of 90.65±4.34.